Role of Intangible Assets in the Adoption of Advanced Manufacturing Technologies (AMT’s) in Developing Countries: Case Study of Uganda. - Mukasa, Norbert; Okure, Mackay A.E.; Elvenes, Bjørn Otto (Second International Conference on Advances in Engineering and Technology, 2011)
This study analyses the machine tool driven industry in a developing country. It models the relationships between measures of Advanced Manufacturing Technology (AMT) penetration, adoption trends and three sets of predictor variables that are intangible. The study was carried out in 39 firms found to be using machine tools. The results show that education levels of blue collar workers, engineers and managers were instrumental to the investment in systems, devices and stations (SDS), while clerical employees are instrumental in integrating these technologies. The Chief Executive Officer (CEO) and environmental issues were strong influences. The strongest single strategic motivation that drove Ugandan firms to invest in AMT’s was the superior image of the firm followed by reduction in labour costs. Finally the study provides interesting insights into the relatively atypical parameters that characterize this industry in a developing country. .
Keywords: Advanced Manufacturing Technologies (AMT), Modelling, Developing countries, Intangible assets